2003
DOI: 10.1016/s0749-596x(02)00513-2
|View full text |Cite
|
Sign up to set email alerts
|

Processing resyllabified words in French

Abstract: In French, the final [ ] of dernier is not pronounced in dernier train (last train), but is pronounced, in the following syllable, in a liaison environment like dernier oignon (last onion). Due to liaison, dernier oignon becomes homophonous with dernier rognon (last kidney). In four pairs of cross-modal priming experiments, French participants made visual lexical decisions to vowel-or consonant-initial targets (e.g., oignon, rognon) following both versions of spoken sentences like C'est le dernier oignon/rogno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
107
3
16

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(140 citation statements)
references
References 50 publications
14
107
3
16
Order By: Relevance
“…This finding adds to a growing body of research that suggests that fine-grained subphonemic information in the speech signal can modulate lexical activation, both in the recognition of individual words (Andruski, Blumstein, & Burton, 1994;Dahan, Magnuson, Tanenhaus, & Hogan, 2001;Marslen-Wilson & Warren, 1994;McQueen, Norris, & Cutler, 1999) and in the recognition of words in continuous speech (Gow, 2002;Gow & Gordon, 1995;Spinelli, McQueen, & Cutler, 2003;Tabossi et al, 2000). Our results are also consistent with Davis et al (2002), who showed that subphonemic cues can be used to resolve ambiguities caused by lexical embedding.…”
Section: Discussionsupporting
confidence: 88%
“…This finding adds to a growing body of research that suggests that fine-grained subphonemic information in the speech signal can modulate lexical activation, both in the recognition of individual words (Andruski, Blumstein, & Burton, 1994;Dahan, Magnuson, Tanenhaus, & Hogan, 2001;Marslen-Wilson & Warren, 1994;McQueen, Norris, & Cutler, 1999) and in the recognition of words in continuous speech (Gow, 2002;Gow & Gordon, 1995;Spinelli, McQueen, & Cutler, 2003;Tabossi et al, 2000). Our results are also consistent with Davis et al (2002), who showed that subphonemic cues can be used to resolve ambiguities caused by lexical embedding.…”
Section: Discussionsupporting
confidence: 88%
“…A number of studies, for instance, have found that assimilated word forms, like greem for English green, are recognized correctly only in assimilation-licensing contexts such as greem bench where the /m/ of greem and the /b/ of bench match in place of articulation (e.g., Coenen, Zwitserlood, & Boelte, 2001;Gaskell & Marslen-Wilson, 1996Gow, 2001Gow, , 2002Mitterer & Blomert, 2003). Similarly, reduced word forms like posman for postman (Ernestus, Baayen, & Schreuder, 2002;Mitterer & Ernestus, 2006;Sumner & Samuel, 2005) or resyllabified forms (e.g., Spinelli, McQueen, & Cutler, 2003;Vroomen & de Gelder, 1999) are recognizable in contexts that license the surface change. All these findings suggest that listeners can recover the underlying form from surface variation, but restoration only happens if the variation occurs in viable contexts.…”
Section: Introductionmentioning
confidence: 99%
“…On peut cependant noter à cet égard que la faiblesse acoustique et perceptuelle des consonnes de liaison, observée notamment par Dejean-de-laBâtie (1993), , Spinelli et al (2002Spinelli et al ( , 2003, Coquillon & Astésano (2008) et , n'appuie pas de façon générale l'analyse morphémique des consonnes de liaison. Certaines études ont montré que les consonnes ayant un statut morphémique sont plus longues que les consonnes identiques non morphémiques, par exemple le [s] flexionnel de l'anglais wrecks par rapport au [s] lexical de Rex (Walsh & Parker, 1983 ;Losiewicz, 1992).…”
Section: Liaison Et Assibilationunclassified
“…Les indices acoustico-phonétiques associés à la liaison peuvent influencer l'accès lexical également dans les énoncés ambigüs au niveau segmental. Spinelli, McQueen et Cutler (2003) [ʁ]oignon < dernier rognon (ambiguë), demi rognon (pas ambiguë), ancien nitrate (contrôle)) ; en outre, les mots cibles à consonne initiale (p.ex. ROGNON) étaient davantage activés lorsqu'ils étaient contenus dans l'amorce que lorsqu'ils n'étaient pas contenus dans l'amorce (p.ex.…”
Section: Introductionunclassified
See 1 more Smart Citation